The Effects of Nano Bentonite and Fatty Arbocel on Improving the Behavior of Warm Mixture Asphalt against Moisture Damage and Rutting - Sepehr Saedi; Seref Oruc (Civil Engineering Journal, 2020)
The use of warm mix asphalt (WMA) technology has increased dramatically in recent years to protect the environment and reduce energy consumption. Despite numerous advantages, WMAs are less commonly used as a result of their lower performance in comparison to HMAs. One of the main reasons for the low performance of WMAs is their high moisture sensitivity. In recent decades, bitumen modifiers have been used to improve the performance of asphalt mixtures. One of the additives that has recently been used to modify the characteristics of bitumen, is bentonite. The grade of asphalt cement used in this study is PG 64 -22 and the Bitumen is modified with 1, 3, 5 and 7% nano bentonite. Also, 0.3% fatty Arbocel has been used for the preparation of WMA. Indirect tensile strength (ITS) test and Nicholson stripping test are used to determine moisture sensitivity and dynamic creep test and LCPC are also used to evaluate the rutting potential. The results indicate that, increasing the percentage of nano bentonite and applying 0.3% of fatty Arbocel improves the resistance of mixture against moisture damage. Also it was found that increasing the mixture hardness decreases the permanent displacement and rutting potential of WMAs. So, it is suggested that the consumption of these additives increases WMA’s lifetime and decreases its maintenance cost.